“Na mata ni Civa au a vakawaletaka” : an ethnobotanical study on kumala (Ipomoea batatas (L.) Lam) and its contribution to climate-smart agriculture in Ra, Fiji : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Horticulture, Massey University, School of Agriculture and Environment, Palmerston North, Aotearoa - Leweniqila, Ilisoni Lasaqa Vuetinabouono (Massey University, 2022)
Globally, sweetpotato (Ipomoea batatas (L.) Lam) or kumala is regarded as an essential, versatile, and under-utilised food security crop. In Fiji, kumala has a strong traditional base, and our ancestors valued this crop as a lifesaver to people during and after natural disasters to act as food security since both the tubers and leaves are consumed. This research weaves together two methodologies; the Fijian Vanua Research Framework (FVRF) which involves ethnobotany studies, and a western sciences (field trials) research element to support and reinstruct smallholder farmers on the value of kumala as a significant crop for subsistence and a source of livelihood for rural economic development in Fiji. The three research sites were Nabukadra (<20m asl ) located in the coastal land area, Bucalevu (>150m asl) in the high altitude inland, and Burenitu (80-100m asl) in the district of Nalawa which is situated at a lower altitude. The implementation of FVRF in this research paid specific attention to indigenous Fijian society aligning to future food security issues in an agricultural context. This research sought a solidarity approach for the rural areas in Fiji adopting their systems of knowledge and perception as the basis for inquiry extending the knowledge base of indigenous people and transforming their understanding of the social-cultural world like solesolevaki, which is our current cultural currency. The Dre’e metaphor was generated to discuss the findings from this research. The findings of this research discussed the cultural role of kumala production in the I-Taukei context under four components: values and beliefs, practices, skills, and knowledge. Indigenous Knowledge (IK) exists across all facets of the I-Taukei way of life, which includes health, belief system, and environmental survival. Given that each genotype or variety of kumala may respond differently to production factors, there was a need to evaluate available sweetpotato genotypes across geographic zones where it can be grown in Fiji. The application of agronomic field trials at different altitudes for this research provided a valuable recommendation that will assist farmers in decision-making for growing kumala at different altitudes in Ra. This will enhance food security and create economic opportunities. Furthermore, this extension of traditional and agronomic knowledge will support climate-smart agriculture (CSA) and help achieve food security in the province of Ra, Fiji Islands.
Keywords: Sweet potatoes; Climatic factors; Food security; Fiji; Ra; 451501 Pacific Peoples agriculture and forestry